Avaliação e disseminação do uso de técnicas do planejamento e controle da produção em uma empresa de saneamento básico - Mendes, Marcelo Henrique Alves (2014)
The aim of the present work is the development of an evaluation method of the level of implantation of Planning and Controlling of Production – PCP and its dissemination, under the view of a functional body of a company. This statement aims at identifying, in a different perspective, strong and weak points of the management of enterprises focusing on the corrective actions maximizing the results. In order to do that, a survey was developed and applied, using for basis the list of 15 good practices, refined by Reck (2010) from Bernardes (2001). The survey mentioned above is made of 58 questions divided in evaluation Ex-Ante, Planning and Controlling of Production and evaluation Ex-Post. It was applied to professionals in the field of planning and controlling, inspection and operation of the works deployed. Due the strategic importance that infrastructure works have either to the growing of economy as to the well being of the population, an engineering company of the mentioned field was chosen to apply the survey, more specifically a basic sanitation company. The methodology used was the survey data, using as tool a quanti-qualitative interview, in which planning processes were analyzed and criticized. In the end, actions to adapt and improve the procedures were pointed from the results of the qualitative research, indicating new fields that are likely to be deeply studied. The quantitative study pointed 4,6 as the overall average reached by the company studied. It means that the company has an average level of practices of PCP. In the qualitative study, the research showed the control as the most developed tool and planning as the least evolved.